A 24-month prospective study on the efficacy and safety of two different monthly regimens of vitamin D supplementation in pre-menopausal women with systemic lupus erythematosus. (April 2015) - Andreoli, L; Dall'Ara, F; Piantoni, S; Zanola, A; Piva, N; Cutolo, M; Tincani, A
Background: Low vitamin D (vit.D) serum levels are common in patients with systemic lupus erythematosus (SLE) and seem to correlate with higher disease activity. We investigated the effects of different regimens of vit.D supplementation in SLE patients with inactive disease. Methods: This 24-month prospective study included 34 SLE women who were randomized to receive, together with their ongoing treatment, a standard regimen (SR) of cholecalcipherol (25, 000 UI monthly) or an intensive regimen (IR) (300, 000 UI initial bolus followed by 50, 000 UI monthly) for one year and then were switched to the other regimen in the second year. Patients were seen quarterly for assessment of 25-OH vit.D levels, disease activity, SLE serology and bone metabolism markers. Results: By intra-patient comparison, only the IR was found able to significantly raise vit.D serum levels. After 12 months, values above 30 ng/ml were found in 75% of patients in IR while in only 28% in SR. No significant differences in disease activity and SLE serology were found at any time point between SR and IR. No changes in the mineral metabolism were observed. Conclusions: The IR was safe and effective in obtaining sufficient levels of vit.D in most SLE patients. However, both regimens of supplementation did not differently affect disease activity nor SLE serology.